From tree to medicine: Cinchona in Tradiciones peruanas and the use of hydroxychloroquine today - Arauco Lázaro, Daniel Andrés (2020)
This article will analyse the story «Los polvos de la condesa». It is proposed that in this text Ricardo Palma deals with the use of cinchona as a natural medicine for the solution of certain ailments in the viceroyalty. In addition, some information on quinine, a compound extracted from cinchona bark, is included. Based on this finding, centuries later, the compound hydroxychloroquine was developed, which attempted to mimic the properties of the plant and is currently used as an antimalarial drug or proposed for the treatment of COVID-19.